Situating Sex, Gender, and Health in South Asia - Faiz Rashid, S.; Desai, S.; Kumar, R. (Springer Nature, 2024)
This first chapter of the handbook begins with a brief account of the beginnings of scholarship and activism on sex, gender, and health, including in South Asia. It introduces key sex/gender concepts before contextualizing them in the varied histories and politics of the region while highlighting recent advances in sexual rights amidst the backlash. Subsequently, the authors provide a road map of approaches to integrating a sex/gender lens into understandings of health and illness, focusing on intersectionality, socioecological approaches, social and structural determinants, and rights-based approaches. While not an exhaustive review, the road map offers a foundational understanding to contextualize the content of the subsequent chapters and sections in this handbook.
Keywords: Gender; South Asia; Health; Intersectionality; Social determinants; Socioecological; Human rights